2022
DOI: 10.1002/cssc.202201543
|View full text |Cite
|
Sign up to set email alerts
|

Water Harvesting Strategies through Solar Steam Generator Systems

Abstract: Solar steam generator (SSG) systems have attracted increasing attention, owing to its simple manufacturing, material abundance, cost‐effectiveness, and environmentally friendly freshwater production. This system relies on photothermic materials and water absorbing substrates for a clean continuous distillation process. To optimize this process, there are factors that are needed to be considered such as selection of solar absorber and water absorbent materials, followed by micro/macro‐structural system design f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 285 publications
(273 reference statements)
0
16
0
Order By: Relevance
“…For typical 2D evaporators, a common issue faced in developing SSG is the huge thermal loss towards the bulk water. 10,21,23 In order to minimize this energy loss, heat isolation is one of the important factors in designing interfacial SSG systems. Besides using a low thermal conductive material as a water absorbing substrate (Fig.…”
Section: Surface Roughnessmentioning
confidence: 99%
See 3 more Smart Citations
“…For typical 2D evaporators, a common issue faced in developing SSG is the huge thermal loss towards the bulk water. 10,21,23 In order to minimize this energy loss, heat isolation is one of the important factors in designing interfacial SSG systems. Besides using a low thermal conductive material as a water absorbing substrate (Fig.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…15,16 Many previous SSG systems have pursued heat generation performance through introducing different types of PTM with potentially a short bandgap for a broader light absorption. 10 Besides this, a recent study has highlighted another important aspect of developing a PTM with high joint density of states (JDOS). The existence of high JDOS allows for high population of hot electrons and holes, promoting higher photoexcitation, broadening the wavelength range for light absorption, as well as a faster relaxation process of the photoexcited carriers.…”
Section: Heat Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, polyvinyl alcohol (PVA) hydrogels containing numerous -OH groups initially proposed by Yu's group 28,29 are most oen employed as SVGs due to their excellent chemical stability and low cost. [30][31][32][33][34][35] Meanwhile, a considerable number of studies have reported SVGs based on other hydrophilic polymer networks, such as -SO 3 H groups in polystyrene sulfonates, 36 -NH 2 groups in polyacrylamides, 37,38 and -C-O-Cgroups in polyethylene glycols. 39,40 Unfortunately, these studies have overlooked the structure-property-application relationship of hydrogel-based SVG systems.…”
Section: Introductionmentioning
confidence: 99%